Plant Secondary Metabolites and Their Therapeutic Properties for Cancer Treatment - Tanaya , Khirabdhi; Singh , Durgeshwer (Socio-Scientific Interaction in Diabetes and Cancer and Its Management, 2023)
Plant secondary metabolites have peculiar roles in an organism such as defense, signaling and transport of metals. These secondary metabolites can induce or inhibit various physiological activities and have been used for treatment of multiple diseases including cancer. The bioactive compounds obtained from plant metabolites play an important role in controlling cancer symptoms and treatments, with minimum side effects. Many plant secondary metabolites related to terpenes, phenolics, nitrogenous and sulfur-containing compounds have anticarcinogenic properties and some are commercially available in the market. The objective of this paper is to study various plant secondary metabolites that have ability to kill or inhibit the cancerous cells and their possible mechanisms involved for the inhibition or killing of cancer cells. The plant secondary metabolites act as bioactive molecules to inhibit or suppress various metabolic pathways related to cancer treatment these compounds are biologically friendly and less toxic to the normal cells. The discovery and development of plant metabolite-based drugs provide a futuristic approach to treatment of cancer.